The Effects of Helicobacter Pylori Eradication on the Number of Tender Points, Sleep Quality, Depression, and Anxiety in Patients With Fibromyalgia - Emrullah GEZİCİ,; Mahmut ALPAYCI,; Yasemin ÖZKAN,; Mehmet Emin KÜÇÜK,; Hakan ÜNVER,; Özcan HIZ, (Archives of Rheumatology, 2014)
Objectives: This study aims to investigate the effects of Helicobacter pylori (H. pylori) eradication on the number of tender points, sleep quality, depression, and anxiety in patients with fibromyalgia syndrome. Patients and methods: The study was performed on 32 fibromyalgia syndrome patients (28 females, 4 males; mean age 38.5±8.6 years) suffering from dyspeptic complaints. All participants were evaluated by gastric endoscopy and bacterial culture for the presence of H. pylori. Patients included in the study were all H. pylori positive. The patients were assessed by the number of tender points, the Pittsburgh Sleep Quality Index, the Beck Depression Inventory, and the Beck Anxiety Inventory pre- and post-treatment for eradication of H. pylori. Amoxicillin 1 g, clarithromycin 500 mg, and lansoprazole 30 mg were given twice daily for three weeks to all patients. Results: The number of tender points was significantly reduced at the evaluation of post-treatment compared with baseline (p<0.001). However, there were no significant differences between pre- and post-treatment for the scores of the Pittsburgh Sleep Quality Index, the Beck Depression Inventory, and the Beck Anxiety Inventory (all p>0.05). Conclusion: Our study results show that H. pylori eradication has a positive impact on the number of tender points.